A case report of a giant rectal adenoma causing secretory diarrhea and acute renal failure: McKittrick-Wheelock syndrome. Issue 1 (December 2016) - Agnes, Annamaria; Novelli, Domenico; Doglietto, Giovanni; Papa, Valerio
Abstract Background The McKittrick-Wheelock syndrome is a rare depletion syndrome caused by a secretory villous adenoma or a carcinoma of the rectosigmoid tract. An aggressive hydroelectrolyte rebalancing is often needed, and curative treatment is obtained only with complete removal of the lesion, by endoscopy or surgery. Low clinical suspicion often delays the diagnosis, resulting in detrimental complications. Case presentation We report the case of a 75-year-old woman, presenting to the emergency department with acute renal failure and electrolyte imbalance, reporting an history of recurrent episodes of dehydration and chronic diarrhea. After being admitted to the nephrology department she underwent diagnostic investigation that revealed the presence of a giant adenoma of the rectum. The patients received supportive therapy and was subsequently treated with surgery, with a favorable outcome. Conclusions A prompt diagnosis plays an important role in the treatment of McKittrick-Wheelock syndrome. We describe a case of this condition in detail and review the related literature, underlining the typical diagnostic features and exploring the possible therapeutic options.